Effect of precipitating events on information system adoption and use behaviour. Issue 5 (19th August 2014) - moghavvemi, sedigheh; Mohd Salleh, Noor Akma
Abstract : Purpose: There were numerous models that were developed with the explicit purpose of predicting the IS adoption behaviour. However, these models are criticized for the fact that they do not accurately capture the effect of external factors (unforeseen events) on individual intention, which may inhibit the act of adopting and using IS. The main aim of this study is to investigate these external factors among entrepreneur(s) and measure how the individual's propensity to use affects the adoption and use of IS innovation. This paper will also attempt to investigate the key determinants of the adoption of IT innovation among entrepreneurs in Klang Valley, Malaysia. Design/methodology/approach: Based on the research model, a questionnaire was developed, and data collected from entrepreneurs based in Klang Valley Malaysia. 326 responses were collected, and the research model was applied using the structural equation modelling technique. Findings: The performance expectancy and the propensity to act are salient determinants of behavioural intention to adopt and use IS innovation. An individual's pervasive decision to use IS innovations are strong factor that influences individual intention and behaviour prediction. Furthermore, precipitating events were determined to be the underlying factor that influences the behavioural intention for an adopter to actually adopt IS innovation(s). The finding(s) demonstrates that the probability of an intention actually translating into actual usage is higher if the precipitating events occur in their respective businesses. Research limitations/implications: It is important to evaluate this study's results and contributions in light of its limitations. This is an initial test for this model, and it should be subjected to further testing and refinement, particularly with regards to the precipitating events construct. One should be aware that an entrepreneur is exposed to various events and challenges that could involve their personal, family, career, and business life. Certain events related to these factors would impact the entrepreneurs differently, which might require different coping mechanisms. Future research should focus on the precipitating events related to their personal, family, career and business life, and which of these precipitating events are most prominently affecting their decision to actively use IS innovation. Practical implications: End-users, particularly, as this study reveals, do prefer new IS innovation, but they may not use it as often. Thus, developers and or inventors of IS innovation need to understand factors that can influence users' decision to adopt and use IS innovation. As for entrepreneurs, understanding factors that influence them to use IS innovation would enhance their sense on the relative importance of using the system. Furthermore, this study provides evidence concerning the role of precipitating events, which encourages or inhibits entrepreneurs toward IS related innovation adoption behaviour. This study makes clear that government policy and environmental factors, as well as work situation significantly influences an entrepreneur's intention in using IS innovation. Originality/value: This study extends the Unified Theory of Acceptance and Use of Technology (UTAUT). Some aspects of the Entrepreneurial Potential Model are incorporated into UTAUT, with the express purposes of capturing external variables. Additionally, the role of the volitional aspect of an entrepreneur's intention toward IS innovation are also taken into due consideration. This model assist the researchers in measuring the effect of pervasive decision and external factors on technology acceptance, and will provide essential information that explains the promotion of IS innovation adoption, usage and hindrance.